2011
DOI: 10.1002/jbmr.387
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin D–binding protein modifies the vitamin D–bone mineral density relationship

Abstract: Studies examining the relationship between total circulating 25-hydroxyvitamin D [25(OH)D] levels and bone mineral density (BMD) have yielded mixed results. Vitamin D–binding protein (DBP), the major carrier protein for 25(OH)D, may alter the biologic activity of circulating vitamin D. We hypothesized that free and bioavailable 25(OH)D, calculated from total 25(OH)D, DBP, and serum albumin levels, would be more strongly associated with BMD than levels of total 25(OH)D. We measured total 25(OH)D, DBP, and serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
314
6
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(347 citation statements)
references
References 55 publications
14
314
6
2
Order By: Relevance
“…The main result of this study was the higher serum VDBP values in acromegaly patients as compared to control subjects, the difference being more pronounced when only patients with active acromegaly were investigated [20]. Indeed, the entity of VDBP increase was not defined, since the authors did not provide information on the normal reference values in their own laboratory and the assay used in this study seems to be different from those already employed by others [8,9]. However, looking at the distribution of VDBP values in patients and control subjects, one could argue that most of the acromegaly patients of Altinova study had elevated VDBP levels, since the median value reported in the patients was above the upper limit of range of control subjects [20].…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…The main result of this study was the higher serum VDBP values in acromegaly patients as compared to control subjects, the difference being more pronounced when only patients with active acromegaly were investigated [20]. Indeed, the entity of VDBP increase was not defined, since the authors did not provide information on the normal reference values in their own laboratory and the assay used in this study seems to be different from those already employed by others [8,9]. However, looking at the distribution of VDBP values in patients and control subjects, one could argue that most of the acromegaly patients of Altinova study had elevated VDBP levels, since the median value reported in the patients was above the upper limit of range of control subjects [20].…”
mentioning
confidence: 81%
“…However, in some conditions such parameter may not represent a reliable marker of vitamin D activity due to modifications of free hormone levels independently of total hormone storage and amount [8][9][10]. Consistently with the free hormone hypothesis, only hormone not bound to protein vectors can exert biological actions [11].…”
mentioning
confidence: 89%
“…The same group found free 25(OH)D concentrations to be better correlated with bone mineral density than the total 25(OH)D concentrations in young adults (10) . Prospective cohort studies have provided evidence that indicates that low concentrations of total 25(OH)D are associated with an increased risk of CVD (11,12) .…”
Section: Al Found That Black Americans Had Lower Total 25(oh)d Concementioning
confidence: 92%
“…Bioavailable 25(OH)D (the free plus albumin bound portions) has been proposed as a better indicator of vitamin D activity (32)(33)(34), possibly explaining discrepancies between findings of vitamin D effect on health outcomes in studies relying on total 25(OH)D. Several studies have identified a strong relationship between bioavailable vitamin D and indicators of vitamin D status such as bone mineral density and parathyroid hormone (32,33). Bioavailable 25(OH)D can be calculated using several equations and a mathematical model, which incorporate 25(OH)D, VDBP, albumin levels, and VDBP binding affinity by haplotype to varying degrees (32)(33)(34). Recently, an assay of free 25(OH)D has become commercially available, and a comparison of the calculated to measured free 25(OH)D showed that a calculation that does not incorporate VDBP binding affinity overestimates the measured levels (35).…”
Section: Low Serum Concentrations Of Total 25-hydroxyvitamin D (25[oh]d)mentioning
confidence: 99%
“…In addition, certain disease states, including diffuse inflammation and critical illness, have been shown to be associated with lower VDBP levels (44,46). VDBP concentration and haplotype influence the proportion of bioavailable vitamin D (32)(33)(34)47), meaning that the biologic activity of vitamin D could be similar in patients with widely different total 25(OH)D levels. We sought to determine VDBP levels and to identify patient-related factors, including genotype, that may influence these levels in critically ill children.…”
Section: Low Serum Concentrations Of Total 25-hydroxyvitamin D (25[oh]d)mentioning
confidence: 99%